Genomic characterization of a blaKPC-2–producing IncM2 plasmid harboring transposon ΔTn6296 in Klebsiella michiganensis - Song, Jian-Mei; Long, Hu-Bo; Ye, Mei; Yang, Bao-Rui; Wu, Guang-Juan; He, Hong-Chun; Wang, Jun-Ling; Li, Hong-Wei; Li, Xiao-Gang; Deng, De-Yao; Li, Bo; Yuan, Wen-Li (Frontiers in Cellular and Infection Microbiology, 2024)
Klebsiella michiganensis is an emerging hospital-acquired bacterial pathogen, particularly strains harboring plasmid-mediated carbapenemase genes. Here, we recovered and characterized a multidrug-resistant strain, blaKPC-2–producing Klebsiella michiganensis LS81, which was isolated from the abdominal drainage fluid of a clinical patient in China, and further characterized the co-harboring plasmid. K. michiganensis LS81 tested positive for the blaKPC-2 genes by PCR sequencing, with blaKPC-2 located on a plasmid as confirmed by S1 nuclease pulsed-field gel electrophoresis combined with Southern blotting. In the transconjugants, the blaKPC-2 genes were successfully transferred to the recipient strain E. coli EC600. Whole-genome sequencing and bioinformatics analysis confirmed that this strain belongs to sequence type 196 (ST196), with a complete genome comprising a 5,926,662bp circular chromosome and an 81,451bp IncM2 plasmid encoding blaKPC-2 (designated pLS81-KPC). The IncM2 plasmid carried multiple β-lactamase genes such as blaTEM-1B, blaCTX-M-3, and blaKPC-2 inserted in truncated Tn6296 with the distinctive core structure ISKpn27–blaKPC-2–ISKpn6. A comparison with 46 K. michiganensis genomes available in the NCBI database revealed that the closest phylogenetic relative of K. michiganensis LS81 is a clinical isolate from a wound swab in the United Kingdom. Ultimately, the pan-genomic analysis unveiled a substantial accessory genome within the strain, alongside significant genomic plasticity within the K. michiganensis species, emphasizing the necessity for continuous surveillance of this pathogen in clinical environments.